Effects of EEG-Neurofeedback in children with Down syndrome - Saodatkhon Salikhova; Kamala Salikhova (Romanian Journal of Neurology)
Background. Down syndrome (DS) is a genetic disorder characterized by varying degrees of mental retardation and neurological complications. Children with DS often experience difficulties with attention, concentration, learning, memory, speech, language, behavior, and physical balance. Methods. This study included 11 children with DS and 10 children with ADHD, aged 6 to 10 years who received treatment at the private clinic “Neyromed Servis” in Tashkent, Uzbekistan. Cognitive functions were analyzed by using Electroencephalography-neurofeedback (EEG-NFB) and the Forbrain headsets. The Wechsler Preschool and Primary Scale of Intelligence and Schulte table were used to assess the effectiveness of non-drug treatment. Results. The utilization of Forbrain headsets enhanced children’s attentiveness as listeners and improved the quality of their voice and speaking. Positive changes in EEG parameters were also registered: theta wave amplitude and theta-tobeta ratio in the frontal lobes decreased significantly. Conclusion. EEG-NFB treatment significantly improved cognitive function, particularly attention, without any side effects in observed children. Moreover, impulsivity as well as hyperactivity decreased gradually. Additionally, after using of the Forbrain method, vocabulary in children improved by 20-40% across all groups.